2017
DOI: 10.1111/cup.12892
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal psoriasiform hyperplasia, an unrecognized sign of folliculitis decalvans: A histological study of 26 patients

Abstract: Epidermal hyperplasia, sometimes psoriasiform and follicular microcysts, are significant histological signs of FD, which have been ignored until now although they seem very common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…In a retrospective histological analysis of 26 patients with FD, the authors found follicular hyperkeratosis in 77%, hyperplasia of the interfollicular epidermis in 92% with a psoriasiform aspect in 88%, plasma cells in infiltrate in 92%, in 42% in large quantities, and hair tufting in 54%. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective histological analysis of 26 patients with FD, the authors found follicular hyperkeratosis in 77%, hyperplasia of the interfollicular epidermis in 92% with a psoriasiform aspect in 88%, plasma cells in infiltrate in 92%, in 42% in large quantities, and hair tufting in 54%. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…Still, this clue may be absent, and there is a need for additional tools to help make a diagnostic distinction between LPP and neutrophil‐poor FD. Recently, previously unrecognized epidermal hyperplasia in FD was described and measured, thereby providing a new histopathologic criterion to diagnose FD 1 . In that report, however, no comparison of the epidermal thickness in FD was made to LPP.…”
Section: Figurementioning
confidence: 99%
“…Likewise, LPP is classified as “lymphocytic.” However, advanced lesions of FD may be neutrophil‐poor, featuring mostly lymphocytes and plasma cells 3 . Neutrophil‐poor FD may also be termed “lymphocyte‐predominant.” In cases of neutrophil‐poor FD, a distinction from LPP may be challenging if not impossible 1,4,5 . One useful clue in distinguishing FD from LPP is the number of fused follicular infundibula in a compound follicle.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Understandably, the result is reduced self-esteem and psychological effects impacting patients' quality of life (4). Histological findings include a dense perifollicular neutrophilic infiltrate, affecting the upper and middle part of the follicle in the acute phase of the disease, evolving to a lympho-plasmocytic nature extending to the advential dermis, with psoriasi-form epidermal hyperplasia, deep follicular microcysts, polytrichia, disappearance of the sebaceous glands and dermal fibrosis in the late-stage (1,5).…”
mentioning
confidence: 99%